If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1y = y + 2 Reorder the terms: 10 + -1y = 2 + y Solving 10 + -1y = 2 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 10 + -1y + -1y = 2 + y + -1y Combine like terms: -1y + -1y = -2y 10 + -2y = 2 + y + -1y Combine like terms: y + -1y = 0 10 + -2y = 2 + 0 10 + -2y = 2 Add '-10' to each side of the equation. 10 + -10 + -2y = 2 + -10 Combine like terms: 10 + -10 = 0 0 + -2y = 2 + -10 -2y = 2 + -10 Combine like terms: 2 + -10 = -8 -2y = -8 Divide each side by '-2'. y = 4 Simplifying y = 4
| (24-x)-(19-2x)=11 | | 4-3(3x-2)=-5 | | x^2-2x-4y+9=0 | | 12y-12=4y+4 | | 5(-2+t)+4= | | z^3=-27 | | 2b-4b=4 | | (8t+13)+(-3t+7)= | | -6+5t= | | 8t-16=40 | | 33-17= | | A=20(3.14)r^2 | | A=20r^2 | | m^2n-mn^2=0 | | 3x+1-4=1 | | (4x+3)(2x^2-9x-5)=0 | | 2n-15n+18=0 | | (x+2)(x+5)(x+8)(x+11)=3640 | | 2n^3-9n^2=0 | | 5x+8x=14 | | -3x^2+4x+1=0 | | 7x-13-6x=10 | | cos(6x)+cos(8x)+cos(18x)+cos(20x)=0 | | -x^2+x+3=0 | | -x+x+3=0 | | 9x+3x-9x=6+8x+11 | | (3w+4)(2w^2+5w-6)= | | 2x+9+2x=-23 | | 0xX=1 | | 3(0)=0 | | 5x+400+9=19 | | x*x-2=0 |